1986
DOI: 10.1085/jgp.88.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel selectivity for divalent and monovalent cations. Voltage and concentration dependence of single channel current in ventricular heart cells.

Abstract: Single channel and whole cell recordings were used to study ion permeation through Ca channels in isolated ventricular heart cells of guinea pigs . We evaluated the permeability to various divalent and monovalent cations in two ways, by measuring either unitary current amplitude or reversal potential (E,e,,). According to whole cell measurements of E,,,,, the relative permeability sequence is Ca" > Sr" > Ba 2+ for divalent ions ; Mg`is not measurably permeant . Monovalent ions follow the sequence Li' > Na' > K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
343
3
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(388 citation statements)
references
References 42 publications
41
343
3
1
Order By: Relevance
“…As previously reported for L-type (Hess, Lansman, and Tsien, 1986) and N-type channels (Carbone and Lux, 1988;Jones and Marks, 1989), we found that the to-CgTx-sensitive channels of chick DRG neurons became significantly permeant to monovalent cations when the extracellular Ca 2+ concentration was reduced below micromolar levels. When no divalent cations were added to the extracellular solution and 1 mM EGTA was included, a sustained inward current was observed upon depolarization to potentials more positive than -55 mV.…”
Section: N Current Carried By Na +supporting
confidence: 87%
“…As previously reported for L-type (Hess, Lansman, and Tsien, 1986) and N-type channels (Carbone and Lux, 1988;Jones and Marks, 1989), we found that the to-CgTx-sensitive channels of chick DRG neurons became significantly permeant to monovalent cations when the extracellular Ca 2+ concentration was reduced below micromolar levels. When no divalent cations were added to the extracellular solution and 1 mM EGTA was included, a sustained inward current was observed upon depolarization to potentials more positive than -55 mV.…”
Section: N Current Carried By Na +supporting
confidence: 87%
“…The ratio of <i Ca > to <i Ba > with 40 mM external divalent cation was ∼1/3 ( Fig. 2D, black vs. red curves), as expected from prior single-channel studies (26,27). Reducing external Ca 2+ yielded progressively smaller currents (Fig.…”
Section: Significancesupporting
confidence: 83%
“…Similar results have been obtained using recombinant T-type (363) and native Ltype channels (161) and suggest that Ca 2ϩ binds with high affinity in the pore and permeates when displaced by a second Ca 2ϩ . A very interesting property of all voltagegated Ca 2ϩ channels is that they become highly permeable to Na ϩ in the absence of Ca 2ϩ .…”
Section: J Single-channel Recordingssupporting
confidence: 81%